Penerapan Prinsip Desain Norman Foster Pada Perancangan Development Research Center Hasil Produksi Turunan Kayu Di Pangkalan Kerinci - Rizky Fariansyah; Yohannes Firzal; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Every architect have their own characteristics on design; simplicity and pay attention in environment and using an advance technology. Norman Foster is one of the architect in designing by using technology and utilizing nature for energy saving. Development Research is a systematic development effort towards designing, developing and evaluating programs, processes and learning products to find the criteria of validity, practicality, and effectiveness. In Pangkalan from the wood raw, it produces a large of wood waste. To reduce the waste, it can be utilize into a useful products, so it was a needed to build a development research center for wood derivatives. The concept design is annual rings, wich is the circle continue, to increase along with the age of the plants. Just like Norman Foster, in process of design about how the design can be sustain and how will responsive to the natural surroundings.This design will be the place for utilitize the waste by using techno;ogy in process of marking.Keyword: Development Research Center, Wood Derivatives Production, Annual Rings